Fecal microbiome profiling of children with Shigella diarrhea from low- and middle-income countries - Yeshun Fan; Yisong Li; Lan Wang; Dan Zhao; Yarui Zhou; Eric R. Houpt; Jie Liu (Microbiology Spectrum, 2025)
ABSTRACT Shigella is one of the leading pathogens causing diarrhea in children globally. Stool culture remains the standard for diagnosing Shigella infections; however, quantitative PCR (qPCR) offers greater sensitivity. In this study, we evaluated the fecal microbiomes of 27 diarrheal children with and without Shigella identified by culture and quantitative PCR, respectively, aiming to characterize the fecal microbiome profiles of children with Shigella diarrhea and to explore the differences in microbiome and the mechanisms associated with the culturability of Shigella. Our results showed that Shigella qPCR positive cases were characterized by a significantly higher abundance of Shigella and other Proteobacteria, alongside a lower abundance of the probiotic genus Bifidobacterium. This profile was associated with specific virulence factors (VFGs) and antimicrobial resistance genes (ARGs), indicating a unique pathogenic module related to Shigella infection. While no significant difference in Shigella abundance was found between the Shigella culture positive and culture negative groups, genera Bifidobacterium and Ligilactobacillus were enriched in the culture positive group. Interestingly, the culture positive group also possessed a higher abundance of virulence factors associated with pathogenicity, likely resulting from the higher copy number of pINV plasmid. The fecal metagenomic analyses from diarrheal children suggested a potentially distinct intestinal microbial profile associated with Shigella infection and a possible correlation between increased pathogenicity and the Shigella culturability. These findings might contribute to a more comprehensive understanding of Shigella pathogenicity and improving diagnostic methods for Shigella.IMPORTANCEDiarrhea represents the fifth leading cause of mortality among children under the age of five, with Shigella representing the second most common pathogen responsible for diarrhea-related mortality. In the current study, we employed metagenomics to comprehensively characterize the fecal microbiome profiles of children infected with Shigella and to investigate the factors affecting Shigella culturability. We identified a distinct intestinal microbial profile associated with Shigella-infected diarrheal children, observed a correlation between increased pathogenicity and the Shigella culturability, and also proposed some potential factors that might promote the in vitro growth of Shigella strains. These findings might provide evidence for improving diagnostic methods for Shigella.